2010
DOI: 10.1007/s11154-010-9144-2
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic β-cell KATP channels: Hypoglycaemia and hyperglycaemia

Abstract: The pancreatic β-cell ATP-sensitive K(+) channel (K(ATP) channel) plays a critical role in glucose homeostasis by linking glucose metabolism to electrical excitability and insulin secretion. Changes in the intracellular ratio of ATP/ADP mediate the metabolic regulation of channel activity. The β-cell K(ATP) channel is a hetero-octameric complex composed of two types of subunits: four inward-rectifying potassium channel pore-forming (Kir6.2) subunits and four high-affinity sulfonylurea receptor 1 (SUR1) subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 69 publications
(96 reference statements)
0
41
0
2
Order By: Relevance
“…KH tedavisinde temel amaç normogliseminin sağ-lanarak beyin hasarının önlenmesidir (16) . Tedavide ilk tercih edilen ilaç insülin salınımını engelleyen diazoksittir (17) .…”
Section: Discussionunclassified
“…KH tedavisinde temel amaç normogliseminin sağ-lanarak beyin hasarının önlenmesidir (16) . Tedavide ilk tercih edilen ilaç insülin salınımını engelleyen diazoksittir (17) .…”
Section: Discussionunclassified
“…GSIS is a combination of glucose reception and insulin secretion functions. A number of studies have examined the genetic basis of diabetes and identified specific genes for insulin production (Melloul et al 2001), insulin reception (Kubota et al 2008;Guo et al 2009;Dobrzyn et al 2010), and GSIS (Pal 2009;Bennett et al 2010). It has been speculated that the genes for these various roles are functionally linked.…”
Section: Introductionmentioning
confidence: 99%
“…5-5.5 u n c o r r e c t e d p r o o f mmol/L (1,2,3). K ATP channels are open at low glucose levels (1). Increased metabolism, resulting in an increased adenosine triphosphate (ATP)/adenosine diphosphate (ADP) ratio, leads to closure of the K ATP channel, depolarisation of the beta cell membrane and subsequent calcium influx through voltage-gated calcium channels.…”
mentioning
confidence: 99%
“…In contrast diabetes occurs if K ATP channels remain open despite high blood glucose concentrations and increased metabolism in the beta cell (1,4). Recessive inactivating mutations of the K ATP channel genes (ABCC8 and KCNJ11) are the most common cause of severe diazoxide unresponsive diffuse CHI which usually requires pancreatectomy (1,10). Patients with dominant mutations of K ATP channel genes, ABCC8 and KCNJ11, may cause variable phenotype ranges from asymptomatic macrosomia, mild diazoxide responsive CHI to severe persistent HH as well as diabetes mellitus in later life (7,8,9,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation